Historicization of myth : the metaphor "Jesus - child of God" and its Hellenistic-Semitic and Greco-Roman background - Stander, Hennie (Hendrik Frederik), 1953- (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2007.